Behavioural lateralisation in reindeer - Espmark, Yngve; Kinderås, Knut (Rangifer, 2002)
Reindeer (Rangifer tarandus) kept in corrals or otherwise forced to clump typically start milling in response to stressing events. This behaviour is generally considered to have an antipredator effect. An inquiry on herd behaviour, to which 35 Norwegian reindeer husbandry districts responded, showed that 32 experienced that corralled rein¬deer consistently circled leftwards, whereas the remaining three reported consistently rightward circling. Regular monitoring of a reindeer herd in central Norway over a two-year period (1993-94), and experimental studies on a fraction of the same herd, revealed the following traits. Free-ranging reindeer showed no right- or left-turning preference during grazing or browsing, but when the reindeer were driven into corrals or forced to clump in the open they invariably rotated leftwards. The circling of corralled reindeer was triggered at an average group size of 20 to 25 animals, apparently independently of the age and sex of the animals. When they dug craters in the snow to reach food, the reindeer used their left foreleg significantly more often than their right. In 23 out of 35 reindeer, the right hemisphere of the brain was heavier than the left. However, in the sample as a whole, the weights of the left and right hemispheres did not differ significantly. Lateralised behaviour in reindeer is thought to be determined by natural and stress induced asymmetries in brain structure and hormonal activity. In addition, learning is probably important for passing on the behaviour between herd members and generations. Differences in lateralised behaviour between nearby herds are thought to be related primarily to different exposure to stress and learning, whereas genetical and environmental fac¬tors (e.g. diet), age structure and sex ratio are probably more important for explaining differences between distant pop¬ulations.